Tourism Development Strategy in the Sembalun Hill Area, Selong Regency, East Lombok - Bagus Syarifuddin Latif; Ramang H. Demolingo; Asyari (International Journal of Economics, Management, Business, and Social Science (IJEMBIS), 2026)
This study aims to explore and analyze the tourism potential in the Sembalun Hill area of Selong, East Lombok. Interviews, observations, and documentation studies were used in this study. The research focused on identifying tourism potential, facilities and infrastructure, promoting tourism potential, tourism service facilities, employment opportunities, and developing tourism potential for the local economy in the Sembalun Hill area. The research method used was qualitative. Data processing showed that tourism potential development is influenced by community awareness, infrastructure and facilities, tourism potential development, and tourism support services. Tourism development analysis was conducted based on the advantages of each region, each with its own distinct characteristics, within the Sembalun Hill area of Mount Rinjani. Long-term research recommendations include several types of employment opportunities, such as food and beverage vendors, souvenir craftsmen, and artists, which will be the mainstay for developing tourism potential in the Sembalun Hill area.